The college wage premium, overeducation, and the expansion of higher education in the UK - Ian Walker; Yu Zhu (Institute for the Study of Labor (IZA), 2005)
This paper provides findings from the UK Labour Force Surveys from 1996 to 2003 on the financial private returns to a degree the college premium. The data covers a decade when the university participation rate doubled yet we find no significant evidence that the mean return to a degree dropped in response to this large increase in the flow of graduates. However, we do find quite large falls in returns when we compare the cohorts that went to university before and after the recent rapid expansion of HE. The evidence is consistent with the notion that new graduates are a close substitute for recent graduates but poor substitutes for older graduates. There appears to have been a very recent increase in the number of graduates getting non-graduate jobs but, conditional on getting a graduate job the returns seem stable. Our results are consistent across almost all degree subjects the exception being maths and engineering where we find that for men, and especially for women, there is a large increase in the proportion with maths and engineering degrees getting graduate jobs and that, conditional on this, the return is rising.
Keywords: I20; J30; 330; human capital; higher education; college premium